Pengaruh Pembinaan oleh Kepala Desa Terhadap Disiplin Kerja Perangkat Desa Darmaraja Kecamatan Lumbung Kabupaten Ciamis - Ridwan Hakiki; Yayan Rudianto; Harinita Harinita (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The study aims to determine the effect of Coaching by the Village Head on the Work Discipline Village Apparatus of Darmaraja Village, Lumbung District, Ciamis Regency. The method used in this study is a quantitative descriptive method. The data used in this study are primary data and secondary data. The population and sample in this study were 11 people by using a total sampling technique. The data analysis technique used includes sample regression analysis, correlation coefficients, coefficients of determination, and t-test. The results of this study indicate that coaching has a significant influence on work discipline, namely 76%. The remaining 24% is influenced by other factors not examined in this study.